El I Congreso de Ciencia y Tecnología como estrategia para fortalecer la publicación científica en la Universidad Técnica de Machala - Rivadeneira Rodríguez, Elmina Matilde (2016)
One of the functions of the Research Center at “Universidad Técnica de Machala” is to propose strategies for the development of research in the institution. With that purpose in mind, the First Convention of Science and Technology, “UTMACH 2015,” was organized in accordance with what is established in the regional research indicators. This event represented an opportunity to publish the results of the research done by professors from the university and other local and international researchers. As a result, three memoires of research were generated and chosen to be published in the next three consecutive issues of “Cumbres” Scientific Journal. In order to be chosen, these works underwent an exhaustive evaluation and selection process from the Publishing Committee of the journal and external evaluators as well prior to the publication of de scientific articles.